No subsolo do Nilismo: literatura e filosofia em Memórias Póstumas de Brás Cubas - LEAL, Mauro Lopes (Universidade Federal do Pará, 2017)
Machado de Assis is, rightly, a great Brazilian writer not only for their creativity and writing, but mostly for his ideas, his attitude toward the values that often are questioned in his works, which could represent a position that far to be just pessimistic, it is geared more to a nihilist pattern of thought and worldview. Question does not always mean destroy. But if the destruction is inevitable if there is to reset other values. Death is not always configured as an end, but can clearly represent the beginning of a new existence. In this work, it will be subject to the issue of nihilism in The Posthumous Memoirs of Bras Cubas, triggering philosophers like Nietzsche, to put them in dialogue with other writers like Dostoevsky, demonstrating that nihilism can not be considered a regional phenomenon, but worldwide, demonstrating that in Brás Cubas, such nihilism converges to other standards and the possibility of resistance through humor, laughter, joy.